Use of Partial Nephrectomy after Acquisition of a Surgical Robot: A Population Based Study. Issue 6 (November 2016) - Weinberg, Aaron C.; Wright, Jason D.; Whalen, Michael J.; Paulucci, David J.; Woldu, Solomon L.; Berger, Stephanie A.; Deibert, Christopher M.; Korets, Ruslan; Hershman, Dawn L.; Neugut, Alfred I.; Badani, Ketan K.
Abstract : Introduction: : The advent of robotics may promote the dissemination of partial nephrectomy, and allow patients to experience survival and functional benefits compared to radical nephrectomy. Therefore, we assessed the impact of hospital acquisition of a robotic surgery platform on the rate of partial nephrectomy recorded in a nationwide database. Methods: : We identified 53, 364 patients with a diagnosis of localized renal cell carcinoma who underwent extirpative surgery from 2006 to 2012 using the Perspective database. Procedures were categorized based on extent of surgery (radical nephrectomy vs partial nephrectomy), approach (open, laparoscopic, robotic) and hospital ownership of a surgical robot. Changes in the proportion of partial nephrectomies performed over time and the effect of acquiring a surgical robot on the proportion of partial nephrectomies performed were assessed with multivariable logistic regression. Results: : Overall 40, 147 (75.2%) radical nephrectomies and 13, 217 (24.8%) partial nephrectomies were performed between 2006 and 2012. The proportion of hospitals using a surgical robot for renal cancer surgery increased from 1.8% in the first quarter of 2006 to 47.7% by the end of 2012. Partial nephrectomy use ranged from 19.1% to 31.2%. More robotic hospitals performed partial nephrectomy than nonrobotic hospitals (29.6% vs 18.0%, p <0.001). After acquisition of a surgical robot the partial nephrectomy rate increased from 16.4% to 34.3% (p <0.001). Hospitals with a robot were more likely to use partial nephrectomy than radical nephrectomy (OR 1.464, CI 1.39–1.54, p <0.001). Conclusions: : While laparoscopic partial nephrectomy remains a challenging operation, this study demonstrates that hospital ownership of a surgical robot is associated with increased use of partial nephrectomy in the treatment of localized renal masses.